Reduction in Pulmonary Vein Stenosis and Collateral Damage With Pulsed Field Ablation Compared With Radiofrequency Ablation in a Canine Model. (September 2020) - Howard, Brian; Haines, David E.; Verma, Atul; Packer, Douglas; Kirchhof, Nicole; Barka, Noah; Onal, Birce; Fraasch, Steve; Miklavčič, Damijan; Stewart, Mark T.
Abstract : Background: Pulmonary vein (PV) stenosis is a highly morbid condition that can result after catheter ablation for PV isolation. We hypothesized that pulsed field ablation (PFA) would reduce PV stenosis risk and collateral injury compared with irrigated radiofrequency ablation (IRF). Methods: IRF and PFA deliveries were randomized in 8 dogs with 2 superior PVs ablated using one technology and 2 inferior PVs ablated using the other technology. IRF energy (25–30 W) or PFA was delivered (16 pulse trains) at each PV in a proximal and in a distal site. Contrast computed tomography scans were collected at 0, 2, 4, 8, and 12-week (termination) time points to monitor PV cross-sectional area at each PV ablation site. Results: Maximum average change in normalized cross-sectional area at 4-weeks was −46.1±45.1% post-IRF compared with −5.5±20.5% for PFA ( P ⩽0.001). PFA-treated targets showed significantly fewer vessel restrictions compared with IRF ( P ⩽0.023). Necropsy showed expansive PFA lesions without stenosis in the proximal PV sites, compared with more confined and often incomplete lesions after IRF. At the distal PV sites, only IRF ablations were grossly identified based on focal fibrosis. Mild chronic parenchymal hemorrhage was noted in 3 left superior PV lobes after IRF. Damage to vagus nerves as well as evidence of esophagus dilation occurred at sites associated with IRF. In contrast, no lung, vagal nerve, or esophageal injury was observed at PFA sites. Conclusions: PFA significantly reduced risk of PV stenosis compared with IRF postprocedure in a canine model. IRF also caused vagus nerve, esophageal, and lung injury while PFA did not.